Experimental and numerical analysis of the assembly and disassembly of an interlocking joint with large diameter pipe applications. (April 2020) - Campos, Urso; Hall, David; Azimi, Mohammadamin; Matthews, John; Alam, Shaurav; Morgan, Christopher; Baghi, Hadi
Abstract: Press-fit interlocking joint technology allows pipe segments with notched male and female ends to be joined by pressing them together using axial force, eliminating the need for circumferential welding or fusing of the segments which considerably increases the installation time in trenchless and micro-tunneling construction. As trenchless installations become more popular, utility owners and engineers seek for a better understanding of the joint strength (disassembly) and force assembly requirements. This paper provides experimental and numerical insights into the mechanical behavior of an interlocking press-fit joint utilized in steel casing pipes used in trenchless and micro-tunneling applications. Four male/female pairs of 914.4 mm (36 in.) outer diameter specimens were joined to determine assembly forces and interlocking feature performance; these four pairs were then pulled apart to determine disassembly forces (joint strength), failure type, and behavior of the joint. The experimental axial forces required to assemble the joints ranged from 205 to 320 kN (46 to 72 kips), and the forces to disassemble the joints ranged from 254 to 365 kN (57 to 82 kips). The experimental results were compared to three different numerical models, which included: axisymmetric, 3-D concentric, and 3-D eccentric. The eccentric model results were found to be in close agreement to the ones obtained experimentally (16% difference in assembly and 5% difference in disassembly). The FEA models revealed the impact that eccentricities and pipe ovality have in the assembly process and joint strength. The evolution of elastic and plastic deformation at the joint would be very difficult to understand using only experimental studies. The experimental and numerical analysis combination provides a path to the optimization of interlocking joints in the trenchless industry.